A Quality of Service Aware Model for Fog Computing - Kamboj, Shikha; Kumar, Jitender (International Journal of Computer Sciences and Engineering, 2019)
Recent years have witnessed the extension of cloud computing paradigm to the IoT devices. In cloud computing, traffic rate and data transmission time are very high which causes delay and reduces Quality of Service. In order to counter these limitations, many researchers introduced a concept of fog layer. The concept of fog layer has many limitations such as the availability of limited number of servers for serving the incoming requests. To counter the resource limitation problem of fog layer, this paper proposes a mechanism which not only utilizes the cloud resources optimally but also helps to maintain the Quality of Service (QoS). The main purpose of this paper is to present Quality of Service aware model for fog computing and decreases SLA violation in fog computing environment. In this paper, we models and evaluate our proposed mechanism in CloudSim- a framework for modeling and simulation.